Severe viral oesophagitis, pharyngitis, and stomatitis as antecedents of ileocecal Crohn’s disease - Boryczka, Grzegorz; Waluga, Marek; Budzyńska, Agnieszka; Kajor, Maciej; Hartleb, Marek (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
We present a 22-year-old male who developed a severe erosive oesophagitis extending to the pharynx and oral cavity without obvious risk factors. Endoscopic image suggested viral aetiology that could not be confirmed by routine serological diagnostics of infections with cytomegalovirus, Epstein-Barr virus, and Herpes simplex virus. The histopathological evaluation also gave no definite clues to the aetiology of the inflammation. Treatment with acyclovir was ineffective, but gancyclovir therapy caused spectacular clinical improvement and healing of erosions. Two months later the patient presented febrile diarrhoea that was a symptom of ileocecal Crohn’s disease proven by endoscopy, enterography, and histopathology. It is the first report of severe viral oesophagitis preceding clinical manifestation of Crohn’s disease. This observation warrants further study towards the viral aetiology of oral, pharyngeal, and oesophageal erosions, frequently associated with Crohn’s disease.